PERANCANGAN IKLAN ANIMASI 3D SABUN ORGANIK ARUM MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Mohamad Roy Tanjung; Sheanny Ocmi Sakti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology has encouraged businesses to utilize more innovative promotional media to increase product appeal. One effective medium is 3D animated advertising, as it can present more realistic, interactive, and communicative visuals than conventional promotional media. This study aims to design a 3D animated advertisement as a promotional medium for Arum Organic Soap using the Multimedia Development Life Cycle (MDLC) method. The MDLC method consists of six stages: concept, design, material collection, assembly, testing, and distribution. At the concept stage, the objectives, target audience, and promotional concept are determined. The design stage produces a storyboard and product visual design. The material collection stage involves gathering various assets such as images, textures, audio, and visual references. Next, the production process is carried out using Blender software, applying fluid simulation techniques to produce more realistic soap visualizations. The product then undergoes a testing phase to ensure visual quality, animation functionality, and content suitability before being distributed through social media. The research results in a 3D animated advertisement design, which is expected to be an attractive, informative, and effective promotional medium for introducing the benefits of Arum Organic Soap to the public and increasing consumer appeal to the product. Keywords: 3D Animation, MDLC, Blender, Fluid Simulation, Promotional Media, Organic Soap.